Deep Brain Stimulation for Arm Tremor: A Randomized Trial Comparing Two Targets. Issue 5 (14th March 2022) - Kvernmo, Nadja; Konglund, Ane E.; Reich, Martin M.; Roothans, Jonas; Pripp, Are H.; Dietrichs, Espen; Volkmann, Jens; Skogseid, Inger Marie
Abstract : Objective: Deep brain stimulation (DBS) of the thalamic ventral intermediate nucleus (VIM) effectively suppresses arm tremor. Uncontrolled studies suggest the posterior subthalamic area (PSA) may be superior. We compared the intra‐individual efficacy of VIM‐ versus PSA‐DBS on tremor suppression and arm function. Methods: We performed a randomized, double‐blind, crossover trial at Oslo University Hospital in patients (18–80 years) with isolated or combined action tremor affecting at least one arm. Four‐contact DBS leads were implanted (bi‐ or unilaterally) with a trajectory to cover the VIM (upper two contacts) and PSA (lower two contacts). Patients were randomized (1:1 ratio) post‐surgery to: Group 1, VIM‐stimulation months 0–3 (period 1), then PSA‐stimulation months 4–6 (period 2); Group 2, PSA‐stimulation first, then VIM‐stimulation. Primary endpoint was the difference in improvement from baseline to the end of the VIM‐ versus PSA‐period in the sum of the dominant arm tremor scores of the Fahn‐Tolosa‐Marin Tremor Rating Scale (FTMTRS), items 5/6 + 10−14. Results: Forty‐five patients were randomized to Group 1 ( n = 23) or 2 ( n = 22). In the primary endpoint per‐protocol analysis (mixed model, n = 40), mean difference in the sum FTMTRS score improvement for the dominant arm was −2.65 points (95% CI −4.33 to −0.97; p = 0.002). The difference in favour of PSA stimulation was highly significant in period 2, but not period 1. Interpretation: Our randomized trial demonstrated that PSA stimulation provided superior tremor suppression compared with VIM stimulation. A period effect reducing tremor for up to three months in both groups was most likely attributed to a post‐surgery stun effect. ANN NEUROL 2022;91:585–601